In Vitro Activity of Caffeic Acid Phenethyl Ester against Different Oral Microorganisms - Rasha AlSheikh; Hamad N. Albagieh; Ismail Abdouh; Hattan Zaki; Amal M. Alzahrani; Hassan S. Halawany; Khalifa S. Al-Khalifa (Applied Sciences, 2022)
This was an in vitro study that aimed to evaluate the antimicrobial effect of the propolis extract caffeic acid phenethyl ester (CAPE) on four different oral microorganisms. Seven different concentrations of CAPE (0.2, 0.5, 1, 1.5, 2, 3, and 4 mg/mL) for use against Staphylococcus aureus, Streptococcus mutans, Streptococcus oralis, and Streptococcus salivarius were determined using minimum inhibition concentration (MIC), minimum bactericidal concentration (MBC), broth microdilution, and well diffusion tests over 1, 3, 6, 12, and 24 h, while NaF at 0.05 percent was used as a positive control. Staphylococcus aureus was most affected by CAPE’s inhibitory effect on bacterial growth, whereas S. mutans was the least affected. S. mutans and S. oralis had similar CAPE MIC and MBC values of 1 mg/mL and 1.5 mg/mL, respectively. The most resistant bacteria to CAPE were S. salivarius and S. aureus, with MIC and MBC values of 3 mg/mL and 4 mg/mL, respectively. S. oralis, followed by S. salivarius, S. mutans, and S. aureus, had the highest viable count following exposure to CAPE’s MBC values, while S. aureus had the lowest. The current results of the inhibitory effect of CAPE on bacterial growth are promising, and the values of both CAPE MBC and MIC against the related four cariogenic bacterial organisms are significant. CAPE can be employed as an adjunct dental hygiene substance for maintaining good oral hygiene, and has a potential therapeutic effect in the field of oral health care.